GENERATION AND ATRACTION TRAVEL IN BOGOR DISTRICT - Nina, Zainab (Universitas Ibn Khaldun Bogor, 2021)
Cibungbulang District has 32.66 km2 area with 15 villages, Ciampea District has 51.06 km2 area with 13 villages, Dramaga District has 24.47 km2 area with 10 villages, and Ranca Bungur District 21.68 km2 area with 15 villages are conterminal districts to Kota Bogor, and are crossed by the main road that connects between West Java Province and Banten Province. The increase of movement in and out of this area affects the number of movements and also the trip generation and trip attraction caused in the four districts such as education centers, offices, hospitals and recreation places. Conduct a Traffic counting survey on the main road sections that begin to be processed based on MKJI 2017 methode. Also using Trip Generation Manual, describe the number of trip generation and trip attraction to MAT. Then, modeled into SATURN Software. So that, the research results are 9,522 trip/hour trip generation with 382,504 smp/hour trip attraction. And has Level of Service on A-F with B level average. This proves the need for improvement and equitable distribution of infrastructure and facilities, traffic infrastructure. And to realize alternative roads and mass transportation